2011
DOI: 10.1363/4323011
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Mothers' Postpartum Contraceptive Use: A Qualitative Study

Abstract: Ongoing follow-up may help reduce adolescent mothers' risk of contraceptive discontinuation postpartum. Increasing use of long-acting methods also may help reduce their vulnerability to gaps in contraceptive use and discontinuation, which increase the risk of unintended pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 20 publications
0
61
0
1
Order By: Relevance
“…[129][130][131][132][133][134][135][136][137][138][139][140] Two of the studies were reported in two papers, Clarke 130,140 and Herrman. 132,133 Context/population…”
Section: Studies Used To Identify Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…[129][130][131][132][133][134][135][136][137][138][139][140] Two of the studies were reported in two papers, Clarke 130,140 and Herrman. 132,133 Context/population…”
Section: Studies Used To Identify Risk Factorsmentioning
confidence: 99%
“…134,139 Seven studies were conducted in the USA, 129,[131][132][133]135,136,138,139 and the participants in five of these were predominantly of African-American and/or Hispanic ethnicity; in the remaining two US studies, the study participants were, in roughly equal proportions, white, African American or Asian/other.…”
Section: Studies Used To Identify Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Wilson, Samandari, Koo, and Tucker (2011) identified barriers to continued contraceptive use in adolescent mothers. In a qualitative study of adolescent mothers and their health care providers on factors influencing the continuation of contraception, though these mothers were highly motivated in the early postpartum to start effective methods of contraception to prevent a repeat pregnancy, lack of parental support, lack of finances, and loss in continuity of care accounted for the failed continued use of contraception.…”
Section: Contraceptive Use Among Adolescent Mothersmentioning
confidence: 99%